Peran Badan Pengawas Pemilu dalam Penanganan Tindak Pidana Pemilu di Kabupaten Simalungun - Michael Richard Siahaan; Isnaini Isnaini; Mirza Nasution (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This paper aims to analyze the role of the Election Supervisory Body and the obstacles faced in handling election crimes in Simalungun Regency. The research method used is descriptive method, while the data analysis technique uses descriptive qualitative. Based on the results of this study indicate that the rule of law regarding the role of the Election Supervisory Body in handling election crimes is stated in Law no. 7 of 2017 concerning General Elections, Election Supervisory Body Regulation No. 7 of 2018 concerning Handling of Findings and Reports of General Election Violations and Bawaslu Regulation No. 31 of 2018 concerning the Integrated Law Enforcement Center. The role of the Election Supervisory Body in handling election crimes in Simalungun Regency has not been fully able to carry out its role in handling election crimes. The obstacles faced by the Election Supervisory Body in handling election crimes are: there are often differences in perceptions in the Gakkumdu Center, there is a large enough opportunity to eliminate evidence, suspects are often uncooperative, and the lack of Bawaslu officers even though the task must be carried out, especially during elections. relatively much.